Leveraging IoT for Enhanced National Security : A Comprehensive Review - Rukmani, Dr. K. V. Rukmani; Lt. Dr. D. Antony Arul Raj; Ms. Shobana N D; Ms. Sandhiya Sivanandan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In an era marked by rapid technological advancement and evolving security threats, the integration of Internet of Things (IoT) technologies has emerged as a pivotal strategy for bolstering national security efforts. The integration of Internet of Things (IoT) technologies into national security frameworks offers unprecedented opportunities for enhancing situational awareness, proactive threat detection, and effective response mechanisms. By deploying IoT devices such as sensors, cameras, and drones across various sectors including border control, critical infrastructure protection, and emergency management, governments can achieve real-time monitoring and data-driven decision-making capabilities. This paper gives a comprehensive review of the use of IoT technologies in national security, including real-time surveillance, border control and critical infrastructure protection. It examines the challenges and propose strategies, including the development of robust regulatory frameworks.